Principle-centered leadership - Covey, Stephen R. (New York : Free Press, 2003)
The author invites business readers to center their professional lives around principles of excellence and quality and discusses the six conditions of effectiveness and the patterns of organizational excellence.
Includes index.
Keywords: Success -- Psychological aspects; Success in business; Leadership